PEMANFAATAN KAIN PERCA SEBAGAI MEDIA PEMBUATAN KARYA BORDIR APLIKASI DI KELAS XI KKBT SMKN 8 PADANG - Bahrun, Viska; Ezriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process of utilizing patchwork fabric as a medium for creating applique embroidery on children's clothing at SMKN 8 Padang, specifically in class XI KKBT. The problem addressed in this study is the high accumulation of leftover patchwork waste from practical productions within the school environment, as well as the students' tendency to rely on new fabrics for embroidery practice. This study utilizes a qualitative method with a case study approach. Data collection techniques in this study include observation and interviews. The results of this study indicate that the process of utilizing patchwork fabric involves three structured stages: the preparation stage, which includes sorting the patchwork materials; the design stage, which involves sketching flora and fauna-themed motifs; and the execution stage, which produces applique embroidery on children's clothing that meets the principles of unity, intensity, and complexity. The creation process employs embroidery techniques using manual sewing machines and a variety of decorative stitch techniques, such as jumping stitch (tusuk loncat), sasak, granit, and suji cair.